Psikolojik danışma ve rehberlik öğrencilerinin boyuneğici davranış ve depresyon düzeylerinin incelenmesi - Korkmaz, Bülent (My University, 2001)
Bu araştırma, boyuneğici davranış ile depresyon arasındaki ilişkiyi, Psikolojik Danışma ve Rehberlik Öğrencileri örnekleminde, bazı sosyo-demografik değişkenlerle birlikte incelemeyi amaçlamıştır. Örneklemi, 303 kız ve 227 erkek olmak üzere toplam 530 üniversite öğrencisi oluşturmuştur. Verilerin elde edilmesinde, Beck Depresyon Envanteri (BDE), Boyuneğici Davranışlar Ölçeği (BEDÖ) ve araştırmacının hazırladığı Kişisel Bilgi Formu kullanılmıştır. Verilerin istatistiksel analizi, bağımsız grup t testi, tek yönlü varyans analizi (ANOVA) ve Pearson çarpım moment korelasyon katsayısı teknikleri kullanılarak yapılmıştır. Araştırmada elde edilen bulgulara göre; boyuneğici davranış ile depresyon arasında sağlam, anlamlı (r=.58; p<.01) ve pozitif yönde bir ilişki vardır. Depresyon kategorik düzeylerine göre, boyuneğici davranış puanları anlamlı derecede farklılaşmaktadır. Boyuneğici davranış kategorik düzeylerine göre de depresyon puanları anlamlı olarak farklılaşmaktadır. Erkeklerin depresyon düzeyleri kızlardan yüksektir. Erkeklerin boyuneğici davranış düzeyleri de kızlardan yüksektir. Öğrenim gördükleri okula göre depresyon düzeyleri anlamlı biçimde farklılaşırken boyuneğici davranış düzeyleri anlamlı bir farklılık göstermemektedir. I. sınıf öğrencilerinin depresyon düzeyleri, IV. sınıflardan daha yüksektir. I. sınıfların boyuneğici davranış düzeyleri de IV. sınıflardan yüksektir. Deneklerin annelerinin eğitim düzeyleri düştükçe depresyon düzeyleri yükselmektedir. Annelerinin eğitim düzeyi düştükçe boyuneğici davranış düzeyleri de yükselmektedir. Babalarının eğitim düzeyi, deneklerin depresyonları ve boyuneğici davranışları için anlamlı bir değişken değildir. Ailelerinin ekonomik düzeyi düştükçe, depresyon düzeyleri yükselmektedir. Aynı şekilde ailenin ekonomik düzeyi düştükçe boyuneğici davranış düzeyleri de yükselmektedir. Ailesinden ayrı kalan deneklerin depresyon düzeyleri, ailesiyle birlikte kalanlara göre daha yüksektir. Ailelerinden ayrı ya da birlikte kalmalarına göre, boyuneğici davranış düzeyleri anlamlı bir farklılık göstermemektedir.

This study investigated whether the relations between the level of depression and the level of submissive behavior among college students of Psychological Counseling and Guidance and the differences among the students were examined by the levels of depression and submissive behavior according to socio-demographical variables. The sample of the study included 303 females and 227 males, total 530 college students of Psychological Counseling and Guidance. The data were collected by using the Beck Depression Inventory (BDI), the Submissive Acts Scale (SAS) and a questionnaire prepared by the researcher. The data were statistical analyzed by t test, one-tail variance analysis (ANOVA) and Pearson product moment correlation techniques. The findings of the study were; there are significant and positive (r=.58, p<.01) relations between submissive behavior and depression. The depression level of male students has been found to be higher than females. The submissive behavior level of male students has been found to be higher than females. The depression level of first grades has been found to be higher than fourth grades. The submissive behavior level of first grades has been found to be higher than fourth grades. The level of depression of the students with the mother's of low education has been found to be higher than the students with the mother's of high education. The level of submissive behavior of the students with the mother's of low education has been found to be higher than the students with the mother's of high education. Their fathers' level of education is not a significantly variable for their levels of depression and submissive behavior. The level of depression of the students who perceived their family as economicaly low level has been found to be higher than the students with a perception of their family economicaly high level. The level of submissive behavior of the students who perceived their family as economicaly low level has been found to be higher than the students with a perception of their family economicaly high level. The depression level of students who stay with their family has been found to be lower than the students without a family. The submissive behavior level of students is not relating the significant difference of whether they were with their family or not.
Keywords: Öğrenciler; Psikolojik Danışma